(untitled) (Applied Biological Research, 2015)
In this study, we synthesized silver nanoparticles (AgNPs) using common weed Tridax procumbense and tested its antifungal activity against Crossandra wilt, caused by Fusarium incarnatum (Desm.) Sacc. AgNPs were synthesized by the reaction of 1.0 mM Ag NO3 and 5% T. procumbense leaf extract. Synthesized AgNPs were first characterized and then their antifungal activity assessed against the pathogen at various concentrations using poisoned food technique. The particle size analysis using particle size analyzer, ESEM and TEM showed that the particles size ranged 17-40 nm and well dispersed, spherical with zeta potential of around 50 mV. AgNPs inhibited mycelial growth at all the concentrations tested (100 - 800 ppm). Complete mycelial inhibition was observed at 800 ppm followed by 98% at 700 ppm. Ultra-microscopic observations revealed that the nanoparticles caused hyphal abnormality and lysis in F. incarnatum. Further, EDX confirmed the presence of silver particles in mycelia indicating that AgNPs penetrated fungal hyphae. These studies confirmed that the method of synthesis is efficient in production of nanoparticles. Antimicrobial activity study revealed a high potential of Tridax leaf extract stabilized AgNPs.